Case report: Efficacy of immunotherapy as conversion therapy in dMMR/MSI-H colorectal cancer: a case series and review of the literature - San-Román-Gil, María; Martínez-Delfrade, Iñigo; Albarrán-Fernández, Víctor; Guerrero-Serrano, Patricia; Pozas-Pérez, Javier; Chamorro-Pérez, Jesús; Rosero-Rodríguez, Diana; Sotoca-Rubio, Pilar; Barrill-Corpa, Ana Maria; Alia-Navarro, Víctor; González-Merino, Carlos; García-de-Quevedo-Suero, Coral; et al. (Frontiers in Immunology, 2024)
Immunotherapy has demonstrated a role in the therapeutic landscape of a small subset of patients with colorectal carcinoma (CRC) that harbor a microsatellite instability (MSI-H) status due to a deficient DNA mismatch repair (dMMR) system. The remarkable responses to immune checkpoint inhibitors (ICIs) are now being tested in the neoadjuvant setting in localized CRC, where the dMMR/MSI-H status can be found in up to 15% of patients, with remarkable results obtained in NICHE2 and 3 trials, among others. This case series aims to report our experience at a tertiary center and provide a comprehensive analysis of the possible questions and challenges to overcome if ICIs were established as standard of care in a neoadjuvant setting, as well as the potential role they may have as conversion therapy not only in locoregional advanced CRC but also in oligometastatic disease.